Harmonia i dysonans : Wokół rozmów z oksfordzkimi filozofami - Polanowska-Sygulska, Beata (2022)
HARMONY AND DISSONANCE: AROUND CONVERSATIONS WITH OXFORD PHILOSOPHERSThis collection consists of six essays that I wrote between 2019 and 2022, and memories of two scholars to whom I owe a great deal. The idea for the book occurred to me after the outbreak of the war between Russia and Ukraine in February 2022. Several months before the invasion of Ukraine I had read John Gray’s Feline Philosophy: Cats and the Meaning of Life (2020). Though this work – like most of Gray’s writings – gave me a lot to think about, I had no intention of putting my thoughts into words. Having published a number of articles on Gray’s philosophy, and above all a substantial monograph, 1 I had decided to confine myself to reading his future publications. Waking up on that memorable morning of 24 February 2022 was like being born into a new world.Trying to come to terms with what had just transpired, I felt the urge to confront it with Gray’s most recent vision of ethical life. This is how my extended essay John Gray’s ethics and the war in Ukraine, written specially for this collection (the idea for which came to me at the same time), originated.